2020
DOI: 10.1167/iovs.61.4.16
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides Derived from the Immune Defense Protein CAP37 Inhibit TLR4 Activation by S100A9

Abstract: Antimicrobial peptides derived from the immune defense protein CAP37 inhibit TLR4 activation by S100A9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Some AMPs can bind to their targets on the surface of macrophages, and then set off cellular signaling pathway and regulate the secretion of pro-inflammatory factors ( Wang et al, 2011 ; Wei et al, 2015 ; Magrone et al, 2018 ; Zeng et al, 2018 ; Kasus-Jacobi et al, 2020 ; Chai et al, 2021 ). Therefore, the binding of Cath-MH to RAW 264.7 cells were evaluated with flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…Some AMPs can bind to their targets on the surface of macrophages, and then set off cellular signaling pathway and regulate the secretion of pro-inflammatory factors ( Wang et al, 2011 ; Wei et al, 2015 ; Magrone et al, 2018 ; Zeng et al, 2018 ; Kasus-Jacobi et al, 2020 ; Chai et al, 2021 ). Therefore, the binding of Cath-MH to RAW 264.7 cells were evaluated with flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…During CA, increased transcriptional expression of S100A9 occurs in the cornea, followed by a release into extracellular space, which enables the inflammatory response to defend against invader microorganisms. The S100A8/A9 heterodimer discloses its pro-inflammation cascade function via RAGE and TLR-4 [ 81 ].…”
Section: Function Of S100 Protein In Host Defense Mechanismmentioning
confidence: 99%
“…Other reports have also shown that LL-37 induced wound healing in the porcine corneal wound model by activation of EGFR signaling via PI3K/Akt and ERK signaling pathways ( Yin and Yu, 2010 ). Cationic antimicrobial protein, CAP37, interacts with TLR4 and promotes corneal re-epithelization in mice ( Kasus-Jacobi et al, 2020 ). Very recently, a dipeptide, isolated from human placental extract has been found to accelerate corneal wound healing both in vitro and in vivo ( Nagata et al, 2015 ).…”
Section: Antimicrobial Peptides and Alternative Therapeutics In Ocular Wound Healingmentioning
confidence: 99%